Relaxor behavior of MgO dispersed-Pb(Mg1/3Nb2/3)O3-PbTiO3 (90/10) nanocomposite thin films - 박동균; Park, J.-W.; Cheong, D.-S.; Lee, J.-K. (IEEE International Symposium on Applications of Ferroelectrics, 2000)
Pb(Mg1/3Nb2/3)O3-PbTiO3 [PMN-PT] films were deposited by the radio-frequency (r.f.) magnetron sputtering technique and post-annealed. The growth of PMN-PT films as a function of MgO concentration in targets, annealing temperature and heating/cooling rate during annealing was studied. The films deposited from 66 mol% MgO excess target showed good perovskite structure in this study. For film deposited from the target with 66mol% MgO excess content and post-annealed conventionally at 750°C for 10 minutes in oxygen flow, preferential (111) orientation of the perovskite phase and pyrochlore phase of less than 3% was observed. And the room temperature dielectric constant was 2500 at 1kHz. Dielectric and structural properties exhibited relaxor-like behavior. Excess MgO in PMN-PT was homogeneously precipitated and dispersed in grain and grain boundary. The number of MgO nano-particles increased with increasing MgO content in PMN-PT targets.